Analisis Pengaruh Media Bahan Bekas Terhadap Keterampilan Motorik Halus pada Anak Usia 5-6 Tahun di PAUD Al Hikmah - Baiq Nuning Sudiarni; I Made Gunawan (Jurnal Paedagogy, 2021)
This study aims to analyze the effect of used material media on fine motor skills of early childhood. This research uses quantitative research. The sample of this study were 15 children aged 5-6 years in class B PAUD Al Hikmah, with a purposive sampling technique. The research instrument used an observation sheet in the form of an assessment rubric. The data analysis technique used a simple linear regression test. The results of this study concluded that there was an effect of used material media on fine motor skills of early childhood in PAUD Al Hikmah.